PENANGGULANGAN KEKERASAN TERHADAP PESERTA DIDIK DALAM LINGKUNGAN SEKOLAH (Studi SMP Negeri 35 Makassar) - Nur Qalbi; Andi Aco Agus; Nurharsyah Khaer Hanafie (Jurusan Pendidikan Pancasila dan Kewarganegaraan (PPKn), 2019)
Abstract, This study aims (1) to determine the forms of violence against students in the school environment. (2) To find out the sanctions given to teachers for violence against students in the school environment. (3) To find out the efforts made by teachers in overcoming student violence in the school environment. To achieve this goal, the researchers used a qualitative approach, the type of descriptive research, the primary data sources were informants consisting of the principal, six teachers, and six students. Secondary data are documents. Data collection techniques used are observation, interviews, and documentation. The data analysis technique used is descriptive qualitative. The results showed that (1) The forms of violence against students in the SMP Negeri 35 Makassar school environment were physical violence including: a) hitting, b) pinching, c) pressing on the ear, and d) throwing using shoes. The form of psychological violence is giving harsh words. (2) the sanctions given by the teacher for violence against students are: a) a verbal warning, and b) a written warning. (3) efforts made by teachers to overcome violence against students are: a) preventive actions (holding dialogues for teachers, parents, and students. And discipline in class), and b) repressive actions.